Samuel in the clouds - Van Eecke, Pieter, 1975-; Clin d'oeil Films (Firm); Fundación Cinemateca Boliviana ([Brussels, Belgium] : Clin d'oeil Films, 2016)
"Bolivian glaciers are disappearing. Samuel, a former worker at the defunct Chacaltaya ski resort, watches from a window on the roof of the world as the snow and ice melt. Clouds walk past his house in the highest point of the Bolivian Andes, to touch La Paz. Everything seems lost, but he hopes that the snow will return. While scientists search for solutions, Samuel invokes the spirits of the sacred mountains. A poetic look at the consequences of climate changes in people's lives." --
With the participation of: Samuel Mendoza, Marta Calle, Miguel Villca, Isabel Moreno & Juan Pablo Ando.
Cinematographer, Johan Legraie ; editors, Octavio Iturbe, Danniel Danniel ; music, Karim Baggili.
In Spanish, Aymara, English.
Won 2016 Chicago International Film Festival Gold Hugo, Documentary Competition
Won 2017 Full Frame Documentary Film Festival, Environmental Award
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 15, 2021)
Keywords: Glaciers -- Bolivia; Climatic changes -- Bolivia; Ski resorts -- Bolivia; Chacaltaya Ski Resort (La Paz, Bolivia); Bolivia -- Environmental conditions; Documentary films; Nonfiction films; Internet videos; Streaming video